The Effect Of Problem-Based Learning Model On Students' Mathematical Representation Ability And Self-Confidence - Pohan, Lisa Rahmadani; Mukhtar, Mukhtar; Simamora, Elmani (Universitas Negeri Makassar, 2025)
This study seeks to determine: (1) the effect of the Problem Based Learning model on students' mathematical representation skills, (2) its effect on students' self-confidence, (3) the effect of initial mathematical ability (High, Medium, Low) on students' mathematical representation skills, (4) its effect on students' self-confidence, and (5) the learning model's interaction with This study is quasi-experimental. This study included MAN 2 Model Medan grade XI students in the 2024/2025 even semester. The study included 34 students from class XI-F2 B, which used the Problem Based Learning model, and class XI-F2 C, which used the expository approach. Research data came from the Initial Mathematical Ability test, mathematical representation ability test, and student self-confidence questionnaire. The data analysis was two-way ANOVA. The data analysis showed that the Problem Based Learning model affected students' mathematical representation skills, self-confidence, and initial mathematical ability (High, Medium, Low). (5) The learning model and initial mathematical aptitude (High, Medium, Low) affect students' mathematical representation ability and self-confidence.